Сравнение условий ведения бизнеса в Чешской Республике и Российской Федерации - Kataev, Egor (2016)
The purpose of my bachelor work is conditions comparison of conducting business activity in the Czech Republic and the Russian Federation. Bachelor work has been divided into two main parts. The first part of work describes basic provisions of laws, processes of registration of the enterprises in both countries, systems of the taxation and accounting. The second part of work provides expert`s estimations and the estimations of real businessmen of the Czech Republic and the Russian Federation.